Treatment of traumatic dental intrusion by surgical repositioning: clinical case report - Saito, Célia Tomiko Matida Hamata [UNESP]; Luvizuto, Eloá Rodrigues [UNESP]; Santos, Cláudia Letícia Vendrame dos [UNESP]; Trevisan, Carolina Lunardelli [UNESP]; Barioni, Sônia Regina Panzarini [UNESP]; Sonoda, Celso Koogi [UNESP]; Poi, Wilson Roberto [UNESP] (My University, 2011)
The prevalence of dental trauma and its consequences are challenging. This article presents a clinical case of a 9-year-old female who was in a bicycling accident and had a dental intrusion of the left maxillary lateral incisor with extensive dislocation. In the emergency department, surgical repositioning of the intruded tooth and a splinting with steel wire and composite resin was performed and the soft-tissue lesions were sutured. Two weeks after the first visit, pulp necrosis was found and endodontic treatment of the intruded tooth was started with a calcium hydroxide dressing. Despite the traumatic nature of the dental injury, the result of treatment was favorable. After 3 years of follow-up, repair of the resorptions and no signs of ankylosis of the teeth involved were evident. Considering the patient's age and the extent of intrusion, it was concluded that surgical repositioning associated with adequate endodontic therapy was an effective alternative treatment for this case.
Keywords: Dental intrusion; dental trauma